Some Relations between Isologic and Varietal Perfect Groups - Shokufeh Lotfi; S. Mostafa Taheri (Journal of Mathematics)
In 1940, Hall introduced the notion of V-isologism, with respect to a given variety of groups ϑ. In the present article, we study the concepts of V-perfect groups, V-subgroup, and V-quotient irreducible groups, with respect to a given variety of groups ϑ. Also we prove and obtain some results.